Coercivity Mechanism and Magnetization Reversal Process in Nanocomposite Pr2Fe14B/α‐Fe Alloy with Phosphorous Addition. Issue 6 (5th February 2023) - Alam, Mehran Khan; Raza, Shahzab; Han, Guangbing; Kang, Shishou
Abstract : An investigation is conducted for the coercivity mechanism in as‐spun Pr2 Fe14 B/α‐Fe ribbons containing different phosphorus (P) prepared at a wheel speed of 30 ms −1 . With the increase of P addition, the volume of the amorphous phase in the ribbons is increased, and the grain size of Pr2 Fe14 B is decreased. The hysteresis loops of the ribbons with 0.1 at% P exhibit a homogeneous magnetization reversal process similar to single‐phase magnet, demonstrating that soft magnetic grains are fully coupled with the hard ones. The highest coercivity of 12.0 kOe (300 K)–38.0 kOe (100 K) is achieved in the ribbon with 0.3 at% P‐addition, which shows weak exchange coupling interaction between grains, and the high coercivity comes mainly from the decoupled hard phase. The values of the microstructure parameter α k α ex in all compositions are less than 0.3 and imply that the main coercivity mechanism is the mixture of the nucleation of reverse domain and domain wall pinning. The minor hysteresis loops and initial magnetization curves show the dominant domain wall pinning in the ribbon with 0–0.1 at% P, nucleation and pinning in the ribbon with 0.3 at% P, and dominant domain nucleation in the ribbon with 0.5 at% P. Abstract : Phosphorous addition increases the volume fraction of amorphous phase and decreases the grain size of 2:14:1 phase effectively in the as‐spun Pr2 Fe14 B/α‐Fe ribbons. The dominant coercivity mechanism in the ribbons changes from domain wall pinning to nucleation of the reverse domain with the increase in phosphorous content from 0 to 0.5 at%.